Exploring Russian Cyberspace: Digitally-Mediated Collective Action and the Networked Public Sphere - Alexanyan, Karina; Barash, Vladimir; Etling, Bruce; Faris, Rob; Gasser, Urs; Kelly, John; Palfrey Jr., John G.; Roberts, Hal (Law, State and Telecommunications Review, 2014)
Purpose ”“ This paper summarizes the major findings of a three-year research Project to investigate the Internet’s impact on Russian politics, media and society. Methodology/approach/design ”“ We employed multiple methods to study online activity: the mapping and study of the structure, communities and content of the blogosphereÍ¾ an analogous mapping and study of TwitterÍ¾ content analysis of different media sources using automated and human-based evaluation approachesÍ¾ and a survey of bloggersÍ¾ augmented by infrastructure mapping, interviews and background research. Findings ”“ We find the emergence of a vibrant and diverse networked public sphere that constitutes an independent alternative to the more tightly controlled offline media and political space, as well as the growing use of digital platforms in social mobilization and civic action. Practical implications ”“ Despite various indirect efforts to shape cyberspace into an environment that is friendlier towards the government, we find that the Russian Internet remains generally open and free, although the current degree of Internet freedom is in no way a prediction of the future of this contested space.